Supplementing Chitosan Oligosaccharide Positively Affects Hybrid Grouper (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂) Fed Dietary Fish Meal Replacement With Cottonseed Protein Concentrate: Effects on Growth, Gut Microbiota, Antioxidant Function and Immune Response - Chen, Guofeng; Yin, Bin; Liu, Hongyu; Tan, Beiping; Dong, Xiaohui; Yang, Qihui; Chi, Shuyan; Zhang, Shuang (Frontiers in Marine Science, 2021)
Nowadays, oligosaccharides have received more attention by virtue of multiple biological activities. Our present study was conducted to investigate improved effects of reducing dietary fishmeal combined with chitosan oligosaccharide (COS) supplementation in hybrid grouper (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂). In this context, seven iso-nitrogenous and iso-lipidic diets were formulated to feed grouper for 56 days. To prepare feed, reference diet (FM group) containing 55% fishmeal was set. Further, concentrated cottonseed protein (CPC) was utilized to replace 45.00% fishmeal protein, then different COS supplementation levels (0%, 0.2%, 0.4%, 0.6%, 0.8% and 1 %) were added. After 8-week breeding trial, Vibrio harveyi was injected to grouper for a 7-day challenge test until the fish stabilized. The results showed that 0.4%-0.6% COS improved weight gain and specific growth rate (P <0.05), but there was no significant difference in survival rate (P >0.05). Compared with FM group, adhesion and breakage of intestinal plica occurred in COS0 group. Height and width of gut fold reached maximum values in COS0.4 group (P <0.05). Microbiome sequencing suggested that there was stable microbiota core in the gut of grouper. With enhancing COS levels, abundance of beneficial bacteria increased, whereas abundance of conditional pathogens rose too; activities of serum glucose oxidase, catalase and total superoxide dismutase increased (P <0.05); in gut tissue, activities of glutathione peroxidase, glutathione reductase and glutamine firstly increased and then decreased (P <0.05); content of lysozyme, acid phosphatase, complement C3, C4 and IgM showed an upward trend (P <0.05). Compared with FM group, expression of IL-1β and TNF-α were up-regulated in COS0 group; gene expression levels of TLR22, TGF-β and Nrf2 showed a trend of increasing firstly and then decreasing (P <0.05). COS supplement reduced the cumulative mortality of grouper suffered from challenge test (P <0.05). In general, present results demonstrated that dietary COS supplementation enhanced growth performance, intestinal health, antioxidant and immune response of grouper fed with low-fishmeal diet. The optimal and appropriate levels of dietary COS supplement were estimated to be 0.45% and 0.4%-0.6% respectively, providing a reference for dietary supplementation development for grouper.